POSTOPERATIVE INTRAABDOMINAL COMPLICATIONS IN COLON CANCER SURGERY COMPLICATED BY BOWEL OBSTRUCTION AND PERFORATION OF THE TUMOR - S. A. Aliev; E. S. Aliev; B. M. Zeinalov (Вестник хирургии имени И.И. Грекова)
The article presents a retrospective analysis of the results of surgical treatment of postoperative intraabdominal complications in 42 patients with colon cancer complicated by bowel obstruction and perforation of the tumor. The pyoinflammatory processes such as peritonitis and abscesses of abdominal cavity took a leading place in the structure of postoperative complications according to the authors. Method of «closed» decompression and intraluminal irrigation of the large intestine without wide opening of organ lumen was developed and applied into practice as perioperative prophylaxis of pyoinflammatory processes. These measures allowed reducing the rate of postoperative intraabdominal complications from 19,2 to 7,7%.